Hierarchies of plant stiffness. (September 2016) - Brulé, Veronique; Rafsanjani, Ahmad; Pasini, Damiano; Western, Tamara L.
Highlights: Structural parameters that vary across multiple length scales define plant stiffness. Stiffness is modulated from whole plant to organ, tissue, cell and cell wall levels. Arabidopsis proposed for comprehensive investigation of factors controlling stiffness. Gradients of stiffness parameters across length scales leads to emergent properties. Tailoring of plant stiffness for crops and fibers is possible through bioengineering. Abstract: Plants must meet mechanical as well as physiological and reproductive requirements for survival. Management of internal and external stresses is achieved through their unique hierarchical architecture. Stiffness is determined by a combination of morphological (geometrical) and compositional variables that vary across multiple length scales ranging from the whole plant to organ, tissue, cell and cell wall levels. These parameters include, among others, organ diameter, tissue organization, cell size, density and turgor pressure, and the thickness and composition of cell walls. These structural parameters and their consequences on plant stiffness are reviewed in the context of work on stems of the genetic reference plant Arabidopsis thaliana (Arabidopsis), and the suitability of Arabidopsis as a model system for consistent investigation of factors controlling plant stiffness is put forward. Moving beyond Arabidopsis, the presence of morphological parameters causing stiffness gradients across length-scales leads to beneficial emergent properties such as increased load-bearing capacity and reversible actuation. Tailoring of plant stiffness for old and new purposes in agriculture and forestry can be achieved through bioengineering based on the knowledge of the morphological and compositional parameters of plant stiffness in combination with gene identification through the use of genetics.